Study case: Cost of a replacement dairy heifer for a research dairy farm - Calvo Hernández, Olga María (2022)
The estimation of the cost of production of a replacement animal for dairy is a fundamental tool for decision making. This process is the basis for establishing the working capital needs that a producer should consider as part of their activity, given that, until an animal reaches its productive stage, it will be a cost-generating element. The objective of this research was to determine the production cost of a replacement animal of the Jersey breed, under a specialized dairy system, at the Alfredo Volio Mata Experimental Station (EEAVM), through a cost accumulation system by activities. For this, the productive stages in breeding, growth, development, and heifers at first calving were segmented. From January to December 2019, measurements were made of each of the activities of each stage, considering the needs for supplies and labor in general tasks, as well as other specific actions of each productive period. With this, a total cost of ₡267,649.37 (US$458.52) was estimated for an animal in the breeding stage; ₡145,628.06 (US$249.48) for growth; ₡236,067.04 (US$404.42) for a calf from 6 to 15 months and for a heifer at first calving it was ₡491,846.69 (US$842.61). In other words, a replacement animal from 0 to 24 months of age means a total cost for the EEAVM of ₡1,141,191.17 (US$1,955.03), where the feed (concentrate and grass) is maintained as the most important cost (42.64%), followed by labor with 36.37%, the remaining percentage is distributed in other costs such as sanitary management, water, cost of current illnesses and electricity.